2007
DOI: 10.1089/cpb.2006.9973
|View full text |Cite
|
Sign up to set email alerts
|

Internet Use Among Chinese College Students: Implications for Sex Education and HIV Prevention

Abstract: The Internet has gained great popularity among Chinese college students, but studies on Internet use behaviors and their relationship with sexual risk perception and behaviors have been limited. A survey was conducted among 1,845 college students in an eastern province of China, in order to assess the pattern of Internet use among Chinese college students, to examine the relationship of Internet use and HIV knowledge and susceptibility, and to explore the relationship of online risk behaviors with sexual statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 22 publications
0
21
1
4
Order By: Relevance
“…Although the state of Internet-based HIV prevention and intervention research is still preliminary in developed countries, some studies have reported promising results of Internet-based HIV prevention programs (Ybarra & Bull, 2007). However, in China, where Internet use has gained great popularity among the young population, very few researchers have developed Internet-based HIV prevention and safer sex education (Hong, Li, Mao, & Stanton, 2007; Xiao et al, 2014). The findings of the current study provide evidence that the Internet may be a promising channel to deliver HIV/AIDS prevention information for the large rural-to-urban migrant population (including FSWs) in China; and Internet-based interventions may be effective in increasing HIV/AIDS knowledge, condom use self-efficacy, and condom use.…”
Section: Discussionmentioning
confidence: 99%
“…Although the state of Internet-based HIV prevention and intervention research is still preliminary in developed countries, some studies have reported promising results of Internet-based HIV prevention programs (Ybarra & Bull, 2007). However, in China, where Internet use has gained great popularity among the young population, very few researchers have developed Internet-based HIV prevention and safer sex education (Hong, Li, Mao, & Stanton, 2007; Xiao et al, 2014). The findings of the current study provide evidence that the Internet may be a promising channel to deliver HIV/AIDS prevention information for the large rural-to-urban migrant population (including FSWs) in China; and Internet-based interventions may be effective in increasing HIV/AIDS knowledge, condom use self-efficacy, and condom use.…”
Section: Discussionmentioning
confidence: 99%
“…The Internet, which was the second preferred information source in our study, may be an important tool to inform the people and to increase their awareness about HIV/AIDS. The projects, including a direct counselling by an interview on the Internet or a communication with HIV related associations or non-governmental organizations as well as the websites to provide correct information about HIV/AIDS [14]. Since people frequently use the Internet to obtain information.…”
Section: Discussionmentioning
confidence: 99%
“…Pues, de todas las ciberagresiones estudiadas, los resultados indican que los hombres puntúan más alto que las mujeres, es decir, ellas son más acosadas que los hombres en todas las agresiones a través del teléfono móvil y de Internet. Estos resultados son coherentes con diferentes estudios (Chapell et al, 2006;Hong, Li, Mao, & Stanton, 2007;Kowalski & Limber, 2007;Li, 2006;Ybarra & Mitchell, 2007) que sugieren que los hombres se involucran con más frecuencia que las mujeres en el ciberacoso, sobre todo en las conductas relacionadas con el hostigamiento y la persecución, como molestar o amenazar mediante las TICs, y de difusión de imágenes degradantes para la víctima (Kowalski, Limber, & Agatston, 2010;Navarro, 2009;Ortega et al, 2008;Sourander et al, 2010).…”
Section: Prevalencia De Cyberbullyingunclassified